PENDETEKSI KADAR ALKOHOL DALAM TUBUH MANUSIA MELALUI HEMBUSAN NAFAS UNTUK PENGEMUDI MOBIL - Langgeng Wijaya; Edy Kurniawan; Didik Riyanto (Universitas Muhammadiyah Ponorogo, 2019)
Alcohol is a drink containing ethanol in it and people who are ordinary alcohol or drinks that can be intoxicating, the impact of consuming this alcohol a lot and one of them is a diversion campaign produced by the driver. From some of these questions, the idea emerged for the detection of